Learning environments for interprofessional education: A micro-ethnography of sociomaterial assemblages in team-based learning. (November 2020) - Bridges, Susan M.; Chan, Lap Ki; Chen, Julie Y.; Tsang, Joyce P.Y.; Ganotice, Fraide A.
Abstract: Background: Teamwork and collaboration are central to interprofessional education but fostering these attributes in large undergraduate cohorts is challenging. Objectives: This study aimed to examine the complexities of IPE group learning processes by examining how the material and intersubjective intertwine when newly formed interprofessional groups (Chinese medicine, medicine, nursing, pharmacy, and social work) synchronously engaged with face-to-face and online learning in a blended, team-based learning environment. Methods: It was a micro-ethnography study using a sociomaterial theoretical lens. We selected two undergraduate interprofessional healthcare student groups within a large scale programme for contrastive video analysis of synchronous spatial and physical configurations, associated talk, and online activity. Results: Video analysis of evolving physical configurations indicated that Group B was spatially more evenly grouped, and physically orientated to an identifiable leader, despite their blinded peer evaluations indicating distributed leadership. Group A faced a critical event at a public forum leading to spatial disruption breaking into subgroups and isolates; however, this group identified one member as a defined leader in the peer evaluations. Conclusions: Based on online scores, we found that peer identification of leaders may influence learning processes but not learning outcomes in the first IPE team meeting. The design of the physical and virtual learning environments contributed to the developing, sociomaterial processes of group cohesion in interprofessional team-based learning.